Commercial insurance as a tool of consumer protection in the Czech Republic - Eva Ducháčková (European Financial and Accounting Journal, 2016)
Guarantee insurance is used by the state to solve some questions of consumer protection. To be specific it is insurance of tour operators against bankruptcy and insurance of employment agencies against bankruptcy. In both cases the insurance covers business risks of businesses and legal entities and that is the reason why the use of guarantee insurance in this context brings about several problems. On the one hand there are theoretical problems which deal with interpretation and explanation of the nature and principles of insurance and their application to insurance products and also problems concerning risk assessment of these products. On the other hand there are problems which deal with practical application and which are connected with the fact that there is no big interest in this kind of guarantee insurance among insurers with regard to their nature. Issues which approach the problem of consumer protection by means of commercial insurance are also related to the perception and understanding of insurance. Consumers demand full insurance coverage, however, taking into account the regulation of insurance market and the nature of insurance it is not possible to guarantee full insurance cover of losses which are caused by bankruptcy of a tour operator or an employment agency.
Keywords: G22; G29; G30; 650; Employment agency; Guarantee insurance; Obligatory insurance; Tour operator